Analyzing the Effectiveness of Green Finance in Developing Economies: The Role of Climate-Linked Investment Strategies (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Green finance has become a key mechanism for mobilizing climate-aligned capital to advance sustainable development objectives. However, in many developing economies, the adoption and effectiveness of green financial instruments remain uneven and underexplored. Existing literature tends to be fragmented, with limited synthesis on how tools such as green bonds, blended finance, and ESG-linked investments generate measurable environmental and developmental impacts. This study addresses that gap by conducting a systematic and integrative review of 67 peer-reviewed articles and policy reports published between 2020 and 2025. Applying PRISMA 2020 guidelines, the review evaluates how climate-linked financial instruments perform across diverse institutional, regional, and sectoral contexts.Findings reveal that green finance effectiveness is significantly shaped by mediating factors like ESG integration and climate risk evaluation, and moderated by institutional quality, regulatory clarity, and investor confidence. While tools such as green bonds and blended finance show strong potential in emissions reduction and resilience-building, structural barriers—such as governance deficits, limited data systems, and fragmented markets—remain persistent in many contexts. The study proposes an integrated conceptual framework and a policy-action roadmap that map the pathways through which green finance contributes to the Sustainable Development Goals (SDGs) and Nationally Determined Contributions (NDCs). It bridges theoretical and applied perspectives, offering actionable insights for policymakers, development finance institutions, and private investors.